Transforming Islamic Education Through Value-Based Leadership: A Narrative Review - Rahman, Gohar (Yayasan Sinergi Kawula Muda, 2025)
This narrative review explores the dynamics of Islamic educational leadership and its influence on institutional quality and transformation. The study aims to synthesize prevailing leadership models, evaluate their integration with Islamic values, and identify systemic enablers and constraints. Literature was gathered systematically from databases such as Scopus, Web of Science, ERIC, and Google Scholar using keywords including